Insights into Interaction of CO\(_2\) with N and B-doped Graphenes - Xuan Huynh, Nguyen Thi; Chihaia, Viorel; Son, Do Ngoc (Communications in Physics, 2022)
Graphene is a promising candidate for CO2 capture and storage. Doping graphene with other elements is an effective way to modify its CO2 storage ability. The literature has shown that the N and B doping could change the adsorption strength of CO2 on the graphene substrate. However, there is no research available to elucidate the adsorption sites and the physical properties underlying the interaction of CO2 with the N and B doped systems. Therefore, this paper is devoted to clarifying the current topic using the self-consistent van der Waals density functional theory calculations. The results showed that the N and B doping increases and decreases the adsorption energy of CO2, respectively. The reason is that there are more peaks of the electronic density of states of CO2 participating in the interaction with the N p orbital than with the B p orbital.